Clinical Benefit of Capsule Endoscopy in Crohn's Disease: Impact on Patient Management and Prevalence of Proximal Small Bowel Involvement. Issue 7 (17th May 2018) - Hansel, Stephanie L; McCurdy, Jeffrey D; Barlow, John M; Fidler, Jeff; Fletcher, Joel G; Becker, Brenda; Prabhu, Nayantara Coelho; Faubion, William A; Hanson, Karen A; Kane, Sunanda V; Kisiel, John B; Loftus, Edward V; et al.
Abstract: Background: Ileocolonoscopy and computed tomography (CT) or magnetic resonance (MR) enterography (CTE/MRE) are utilized to evaluate patients with small bowel (SB) Crohn's disease (CD). The purpose of our study was to estimate the impact of capsule endoscopy (CE) on patient management after clinical assessment, ileocolonoscopy, and CTE/MRE. Methods: We prospectively analyzed 50 adult CD patients without strictures at clinically indicated ileocolonoscopy and CTE/MRE exams. Providers completed pre- and post-CE clinical management questionnaires. Pre-CE questionnaire assessed likelihood of active SBCD and management plan using a 5-point level of confidence (LOC) scales. Post-CE questionnaire assessed alteration in management plans and contribution of CE findings to these changes. A change of ≥2 on LOC scale was considered clinically meaningful. Results: Of the 50 patients evaluated (60% females), median age was 38 years, median disease duration was 3 years, and median Crohn's Disease Activity Index (CDAI) score was 238 points. All CTE/MRE studies were negative for proximal disease. CE detected proximal disease in 14 patients (28%) with a median Lewis score of 215 points. CE findings altered management in 17 cases (34%). The most frequent provider-perceived benefits of CE were addition of new medication (29%) and exclusion of active SB mucosal disease (24%). Conclusion: CE is a safe imaging modality that alters clinical management in patients with established SBCD by adding incremental information not available at ileocolonoscopy and cross-sectional enterography.